2020
DOI: 10.1111/odi.13432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of smoking and alcohol history in young age oral cavity cancer

Abstract: Objective To assess prognostic factors of patients with operable oral cavity squamous cell carcinoma (OSCC), focusing on the associations with smoking/alcohol exposure and age. Materials and Methods A total of 247 patients with OSCC who received curative surgery ± adjuvant radiotherapy were analyzed. The patient subgroups were divided according to pretreatment smoking/alcohol exposure. Individuals aged 45 years or less were classified as younger patients. Results The median follow‐up was 52.2 months. The 5‐yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
4
10
0
Order By: Relevance
“…Altogether, these findings support the hypothesis that the traditional risk factors can be responsible for just a small proportion of cases of oral cancer among young people and that factors other than tobacco and alcohol are implicated (Al‐Amad, Awad, & Nimri, 2014; Dalla Torre et al., 2018; Fan et al., 2014; Guidry, Birdwell, & Scott, 2018; Lee et al., 2020; Llewellyn, Linklater, Bell, Johnson, & Warnakulasuriya, 2003; Llewellyn, Bell, Johnson, & Warnakulasuriya, 2004; Purwanto et al., 2020; Toporcov et al., 2015; Vidal Loustau et al., 2019).…”
Section: Have You Ever Had a Diagnosis Of Genital Herpes? Have You Evsupporting
confidence: 67%
“…Altogether, these findings support the hypothesis that the traditional risk factors can be responsible for just a small proportion of cases of oral cancer among young people and that factors other than tobacco and alcohol are implicated (Al‐Amad, Awad, & Nimri, 2014; Dalla Torre et al., 2018; Fan et al., 2014; Guidry, Birdwell, & Scott, 2018; Lee et al., 2020; Llewellyn, Linklater, Bell, Johnson, & Warnakulasuriya, 2003; Llewellyn, Bell, Johnson, & Warnakulasuriya, 2004; Purwanto et al., 2020; Toporcov et al., 2015; Vidal Loustau et al., 2019).…”
Section: Have You Ever Had a Diagnosis Of Genital Herpes? Have You Evsupporting
confidence: 67%
“…Eleven studies compared the treatment outcomes of OCSCC between SD and NSND groups 4,11,13,18,20,22,23,27,28,33,34 . Most patients were treated primarily via surgical intervention with or without adjunctive chemoradiation (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies compared the treatment outcomes of OCSCC between SD and NSND groups. 4,11,13,18,20,22,23,27,28,33,34 Most patients were treated primarily via surgical intervention with or without adjunctive chemoradiation (Table 4). Overall survival and recurrence-free survival assessed mostly among young OCSCC patients yielded no marked difference in the cumulative rates observed between NSND and SD groups.…”
Section: Treatment Outcomes and Tumor Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…The malignant transformation rate of OL is higher in non-smokers than in smokers [11][12][13][14][15]. However, although some recent reports [16,17] have shown that non-smokers with OSCC may have a worse prognosis, HNSCC is traditionally associated with better overall survival in non-smokers [18]. Non-smoking HNSCC patients had a significantly greater proportion of programmed death-ligand 1 (PD-L1)-positive cells in the microenvironment of HNSCC and had a higher response rate to anti-programmed death 1 (PD-1) checkpoint inhibitors than smoking HNSCC patients [19,20].…”
Section: Introductionmentioning
confidence: 99%